Counseling Prevention and Intervention Yogurt of Dragon Juice for Diabetes Mellitus - Silawati, Vivi; Mona , Arisa; Franisia, Chitra Ayuni; Fauziah, Ditha; Ningsih, Surtiya; Wulansari, Hastin Catur; Amalya, Novi (Rajaki of Tulip Medika Publisher, 2023)
Background: Integrated Development Post (Posbindu) Neighbourhood 10 and 13 in 2023 the coverage of the elderly without diabetes mellitus is 87%, while the expected target of pregnant women who do not have diabetes mellitus is 90%. In the field, it shows the elderly with diabetes mellitus as much as 13%. One solution to overcome anemia in mothers by non-pharmacological means with the innovation of dragon fruit juice and yogurt. Objective: The purpose of community service is to educate the elderly about the importance of paying attention to blood sugar levels. Methods: community service followed by 10 elderly people, for experiments (getting dragon fruit juice and yogurt innovations). As an indicator to measure the success of giving dragon fruit juice and yogurt innovations to prevent diabetes mellitus in the elderly. Results: The implementation of community service activities begins with preparing educational materials in the form of power point materials and demonstrations of making innovations. After being given educational materials, tell pregnant women to make innovations at home so that they can consume them every day. The next 7 days will be observed every day by the implementation team of this community service activity. Conclusion: The innovations provided in the form of dragon fruit juice and yogurt are useful for reducing diabetes mellitus in the elderly.